Analisis Semiotika Foto Jurnalistik Tragedi Sepak Bola Di Stadion Kanjuruhan Pada Media Online detik.com - Andre Yusup; Nuraida; Muzaiyanah (CV. ITTC INDONESIA, 2024)
This research is entitled Semiotic Analysis of Journalistic Photos of the Football Tragedy at Kanjuruhan Stadium on the Online Media Detik.Com. The Kanjuruhan tragedy is a bloody football tragedy which resulted in many victims falling and hundreds of lives lost. This bloody tragedy occurred on October 1 2022 at the Kanjuruhan Stadium in Malang. Detik.com. The aim of the research is to find out how the analysis of photojournalism published by online media detik.com regarding the Kanjuruhan Tragedy at the Kanjuruhan Stadium in Malang is explained through signifiers and signifieds. This research uses qualitative research methods with a research approach by Ferdinand De Saussure. Then this research uses primary and secondary data types. Data collection techniques use observation and documentation methods. This research concludes that every photo of the Kanjuruhan Tragedy that has been examined has a fairly representative meaning in depicting the atmosphere at the time the Kanjuruhan Tragedy occurred. These several photos can explain to us how scary and terrible it was when the tragedy was taking place.